Ebola Calls for Greater Transparency during Epidemic Emergencies - Chan, Crystal; Tran, Maxwell; Kwong, Michelle (The Meducator, 2014)
The McMaster Health Forum strives to be a leading hub for improving health outcomes at the regional and provincial level in Canada. Through problem-solving and discussion, they harness information, convene stakeholders, and prepare action-oriented leaders to meet pressing health issues creatively.